2012
DOI: 10.5581/1516-8484.20120073
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte, red blood cell and morphological adaptation to moderate physical training in rats undernourished in the neonatal period

Abstract: Objective To analyze the impact of moderate physical exercise on the total and differential leukocyte counts and red blood cell count of 36 sixty-day-old adult male Wistar rats subjected to early malnourishment. Methods The rats were divided in nourished (N - casein 17%) and malnourished groups (M - casein 8%) and thesegroups were then subdivided in trained (T) untrained (U) creating four groups NT, NU, MT and MU. The NT and MTgroups were submitted to moderate physical exercise using a treadmill (60 min/day, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…In the study conducted by Yoshihiro, serum albumin levels were significantly increased after long-term endurance training ( 56 ). Although Marcelo recently demonstrated that moderate physical exercise increases total leukocyte count, it was found that there was no difference in the hemoglobin, hematocrit, and red blood cell count between the trained and untrained groups ( 57 ). The results of this study found that nutrient parameters, such as prealbumin, albumin, and TLC, in these two groups did not show significant differences on the fourth and seventh days after early bedside cycle exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study conducted by Yoshihiro, serum albumin levels were significantly increased after long-term endurance training ( 56 ). Although Marcelo recently demonstrated that moderate physical exercise increases total leukocyte count, it was found that there was no difference in the hemoglobin, hematocrit, and red blood cell count between the trained and untrained groups ( 57 ). The results of this study found that nutrient parameters, such as prealbumin, albumin, and TLC, in these two groups did not show significant differences on the fourth and seventh days after early bedside cycle exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely reason for this is that the level of albumin is likely to be affected by nutritional status and also by inflammation and infection, which restricts its application as a detection marker for critically ill patients. Moreover, albumin has a long elimination half-life, which limits its usefulness in evaluating short-term changes in both energy and protein intake ( 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…A special haematocrit reader card (Hct; %) was used to evaluate the ratio of RBC to total blood volume, as previously proposed by Viana et al. (2012).…”
Section: Methodsmentioning
confidence: 99%
“…At room temperature, the tubes were centrifuged for 5 min at 15,000 g (Centribio microfuge, Biosystems, Curitiba, PR, Brazil). A special haematocrit reader card (Hct; %) was used to evaluate the ratio of RBC to total blood volume, as previously proposed by Viana et al (2012).…”
Section: Blood Collection and Haematocrit Analysismentioning
confidence: 99%
“…Leukocyte counts can easily be studied by TEM and with the advancing age of mice the results may be different. There are several forms of causing undernourishment in animals with the most common being protein malnutrition caused by the ingestion of small quantities of milk protein - casein (about 8%), as described in the original article by Viana et al published in this issue of the Revista Brasileira de Hematologia eHemoterapia ( 5 ) .…”
mentioning
confidence: 99%